Historical development of public charity - Галай, А. О. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Article reveals the historical development of public charity, analyzes its organizational features in theU.S., Europe and the ukrainian lands.